2012
DOI: 10.1111/j.1751-553x.2012.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented red blood cells automated measurement is a useful parameter to exclude schistocytes on the blood film

Abstract: Our study validated the utility of the immediately available FRC parameter on ABCC to exclude schistocytes and the diagnosis of TMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 18 publications
4
42
0
Order By: Relevance
“…An overestimation of the schistocyte count was also noted in the presence of anisopoikilocytosis. This is consistent with other reports that found that the ADVIA and Sysmex (Roche Diagnostics, Kobe, Japan) analyzers underestimated the schistocyte count after a threshold of 1.5% [6,7,14]. However, conditions such as hemoglobinopathies and renal failure represented a small percentage of the study population.…”
Section: Discussionsupporting
confidence: 92%
“…An overestimation of the schistocyte count was also noted in the presence of anisopoikilocytosis. This is consistent with other reports that found that the ADVIA and Sysmex (Roche Diagnostics, Kobe, Japan) analyzers underestimated the schistocyte count after a threshold of 1.5% [6,7,14]. However, conditions such as hemoglobinopathies and renal failure represented a small percentage of the study population.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the FRC parameter could be particularly useful from automated CBCs. However, even when a manual differential count is performed, there is technician variation in reporting schistocytes [5]. Table 3 illustrates this variation in our own data, indicating that when the FRC is very high, schistocytes and other abnormally shaped RBC forms are not always reported.…”
Section: Discussionmentioning
confidence: 82%
“…Certainly the FRC count does not represent an automated count of schistocytes only, and if a precise schistocyte evaluation is needed, a film review is needed. However, in studies of adults, automated and manual values tended to correlate well [5,[23][24][25]. Also, we had relatively few very premature neonates in our database.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations